The Politics of Fossil Fuel Subsidies and their Reform (Cambridge University Press, 2022)
This comprehensive volume focuses on the politics of fossil fuel subsidies and provides insights from numerous case studies, applying a variety of political and economic theoretical approaches. Ideal for researchers, practitioners, and students of political science, international relations, and public policy. This title is also available as Open Access.